2014
DOI: 10.1016/j.ajog.2014.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and gestational diabetes are associated with placental leptin DNA methylation

Abstract: OBJECTIVE In this study, we aimed to investigate relationships between maternal prepregnancy obesity and gestational diabetes mellitus and placental leptin DNA methylation. STUDY DESIGN This study comprises data on 535 mother-infant dyads enrolled in the Rhode Island Child Health Study (RICHS), a prospective cohort study of healthy term pregnancies. Prepregnancy body mass index was calculated from self-reported anthropometric measures and gestational diabetes mellitus diagnoses gathered from inpatient medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 37 publications
5
62
3
1
Order By: Relevance
“…18,19 Discrepancies between previous observations might be due to variations in cellularity of placenta tissues 32 and/or to the impact of GDM treatments on their specific epigenetic profiles. These potential confounding factors were not considered in neither of previous studies.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…18,19 Discrepancies between previous observations might be due to variations in cellularity of placenta tissues 32 and/or to the impact of GDM treatments on their specific epigenetic profiles. These potential confounding factors were not considered in neither of previous studies.…”
Section: Discussioncontrasting
confidence: 44%
“…17 A few observational studies have investigated associations between maternal glycemia and offspring DNAm in LEP genomic region, yet with contradictory findings in direction of effect. 18,19 Observational studies using GDM or maternal glucose levels as exposure are limited by measurement errors and confounding as any other epidemiological studies based on biochemical markers. While it does not allow the establishment of causality with certainty, the Mendelian randomization (MR) approach has the potential to improve causal inference.…”
Section: Introductionmentioning
confidence: 99%
“…17 It has been shown that the LEP promoter is subject to epigenetic programming and that the expression of leptin can be modulated by DNA methylation. 18 For example, in utero exposure to famine and gestational diabetes has been associated with offspring LEP promoter hypermethylation in blood of adults 11 and placental LEP hypermethylation, 19 respectively. According to Lesseur et al, 12 cord blood LEP methylation was higher in small for gestational age infants and lower in infants born to pre-pregnancy obese mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Most An adverse intrauterine environment, complicated by either undernutrition [14] or overfeeding [15], may programme harmful metabolic consequences later in life through epigenetic modifications such as DNA methylation. For instance, maternal gestational glycaemia concentrations correlate with placental DNA methylation adaptations of LEP (leptin) [16,17], ADIPOQ (adiponectin, C1Q and collagen domain-containing) [18] and ABCA1 (ATPbinding cassette transporter A1) [19] genes. Although the tenet of fetal metabolic programming has been extensively explored in animal models [20,21], only a small number of studies on epigenetic modification have been conducted in humans, especially in those with GDM.…”
Section: Introductionmentioning
confidence: 99%